A scoping review of the barriers and facilitators to accessing and utilising mental health services across regional, rural, and remote Australia - Bianca E. Kavanagh; Kayla B. Corney; Hannah Beks; Lana J. Williams; Shae E. Quirk; Vincent L. Versace (BMC, 2023)
Abstract Background Inadequate healthcare access and utilisation are implicated in the mental health burden experienced by those living in regional, rural, and remote Australia. Facilitators that better enable access and utilisation are also reported in the literature. To date, a synthesis on both the barriers and facilitators to accessing and utilising mental health services within the rural Australian context has not been undertaken. This scoping review aims to (1) synthesise the barriers and facilitators to accessing and utilising mental health services in regional, rural, and remote Australia, as identified using the Modified Monash Model; and (2) better understand the relationship between barriers and facilitators and their geographical context. Methods A systematic search of Medline Complete, EMBASE, PsycINFO, Scopus, and CINAHL was undertaken to identify peer-reviewed literature. Grey literature was collated from relevant websites. Study characteristics, including barriers and facilitators, and location were extracted. A descriptive synthesis of results was conducted. Results Fifty-three articles were included in this scoping review. Prominent barriers to access and utilisation included: limited resources; system complexity and navigation; attitudinal and social matters; technological limitations; distance to services; insufficient culturally-sensitive practice; and lack of awareness. Facilitators included person-centred and collaborative care; technological facilitation; environment and ease of access; community supports; mental health literacy and culturally-sensitive practice. The variability of the included studies precluded the geographical analysis from being completed. Conclusion Both healthcare providers and service users considered a number of barriers and facilitators to mental health service access and utilisation in the regional, rural, and remote Australian context. Barriers and facilitators should be considered when re-designing services, particularly in light of the findings and recommendations from the Royal Commission into Victoria's Mental Health System, which may be relevant to other areas of Australia. Additional research generated from rural Australia is needed to better understand the geographical context in which specific barriers and facilitators occur.